The Role of The Social Services in Empowering Persons with Disabilities in Sikka District - Emanuel, Kristianus; Djonu, Amir; Syahrun, Muhammad (Jurnal Riset Ilmu Pendidikan, 2023)
This study aims to determine the extent of the role of the Social Service in Empowering Persons with Disabilities in Sikka District and what are the factors that hinder the Social Service in empowering persons with disabilities in Sikka District. This research method was carried out with a qualitative descriptive approach. The data sources used are primary data sources and secondary data sources. The informants involved in this study were at the Sikka District Social Service. Data collection techniques used are observation techniques, interviews and documentation. Data analysis techniques include data reduction (data reduction), data display (data presentation), conduction drawing (verification). The results of the study show that the role of the Sikka Regency Social Service as a facilitator, motivator and dynamicator and the inhibiting factors are budget, human resources, land ownership status and promotional media. The tasks carried out by the tourism and culture service as well as the village government can be said to be quite effective and maximal enough in carrying out their duties by providing motivation, training and continuing to make improvements which will later bring about changes in the tourism secto